Hospital volunteers – are they satisfied? - Ferreira, Marisa R. (2013)
We examine satisfaction with HRM practices, namely recruitment, training and rewarding in NPO’s and attitudes regarding the appropriateness of these practices. The participants in this study are 76 volunteers, affiliated to 4 different NPO’s, which work in hospitals and have direct contact with patients and their families. Analysing aggregate results we show that volunteers are more satisfied with training, and consider that the training strategies are very appropriate. After identifying differences between organisations we discover that in some organizations volunteers are satisfied with rewards, but in opposition they have negative attitudes regarding the appropriateness of the recognition strategies and vice-versa an opposite relation between satisfaction with reward and recognition strategies and the process of reward and recognition. We also name the more and less satisfied volunteers.